Combining Photoredox and Metal Catalysis. Issue 3 (8th December 2014) - Hoffmann, Norbert
<x xml:space="preserve">Abstract</x> A photogenic pair: Photoredox catalysis with visible light and molecular oxygen as oxidant in combination with palladium catalysis enables highly efficient activation of CH bonds. Mild photochemical reaction conditions generally facilitate the combination of different catalytic reactions.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>